2001
DOI: 10.1016/s0893-133x(01)00346-3
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Ketamine Effects by Nimodipine Pretreatment in Recovering Ethanol Dependent Men Psychopharmacologic Implications of the Interaction of NMDA and L-Type Calcium Channel Antagonists

Abstract: Ketamine blocks the calcium channel associated with N-methyl-D-aspartate (NMDA) glutamate receptors. It has transient behavioral effects in healthy humans that resemble aspects of schizophrenia, dissociative disorders, and ethanol intoxication. Ethanol is an antagonist of both NMDA receptors and L-type voltage-sensitive calcium channels (VSCC) and it has minimal psychotogenic activity in humans. A double-blind placebo-controlled study was conducted that evaluated whether pretreatment with the L-type VSCC antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 55 publications
(73 reference statements)
1
34
0
2
Order By: Relevance
“…Alternatively, these responses could reflect network consequences of alterations in NMDA receptor function, such as the stimulation of the release of glutamate and dopamine (29). Clinical evidence has shown that drugs that attenuate glutamate release or glutamatergic excitability via blockade of voltage-gated cation channels reduce the dysphoric effects of ketamine and promote the euphoric effects of ketamine in both healthy subjects (30) and recovering ethanol-dependent patients (31). In fact, pretreatment with calcium channel blockers in individuals with no family history of ethanol dependence leads to a ketamine response that is more consistent with that of individuals who have a family history of ethanol dependence (30), suggesting that the alteration reflects dysfunction related to voltage-gated cation channels.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these responses could reflect network consequences of alterations in NMDA receptor function, such as the stimulation of the release of glutamate and dopamine (29). Clinical evidence has shown that drugs that attenuate glutamate release or glutamatergic excitability via blockade of voltage-gated cation channels reduce the dysphoric effects of ketamine and promote the euphoric effects of ketamine in both healthy subjects (30) and recovering ethanol-dependent patients (31). In fact, pretreatment with calcium channel blockers in individuals with no family history of ethanol dependence leads to a ketamine response that is more consistent with that of individuals who have a family history of ethanol dependence (30), suggesting that the alteration reflects dysfunction related to voltage-gated cation channels.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in membrane depolarization by blockade of voltage-gated ion would be expected to reduce the extent to which these receptors were in the 'active state,' where they were responsive to the binding of glutamate and glycine. 91 Preliminary analyses also suggest that the alpha-2 adrenergic agonist, guanabenz, attenuates the psychotic and cognitive effects of ketamine in healthy subjects. 93 Another alpha-2 agonist, clonidine, has been reported to have some antimanic effects, although perhaps less than lithium.…”
Section: Molecular Psychiatrymentioning
confidence: 96%
“…For example, lamotrigine and nimodipine attenuate the magnitude of the psychosis, attention impairment and memory impairment produced by ketamine in human subjects. 90,91 In contrast, lamotrigine may have increased the euphoric and stimulatory effects of ketamine. It is not yet clear whether the enhanced euphoric response to ketamine reflects a limitation of lamotrigine in treatment of mania or its prominent antidepressant effects.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…In particular, the changes in ketamine response observed in patients in this study are reminiscent of the impact of pretreatment with an antagonist of voltage-gated cation channels on ketamine response. Both lamotrigine and nimodipine reduce the dysphoric effects of ketamine and preserve or promote its euphoric effects in both healthy subjects (Anand et al, 2000) or recovering ethanol-dependent patients (Krupitsky et al, 2001). The effects of lamotrigine were thought to reflect, in part, its capacity to reduce the stimulatory effects of ketamine on glutamate release.…”
Section: Commentarymentioning
confidence: 99%